Pelatihan Pengolahan Minuman Berbahan Lokal Menjadi Produk Bernilai Ekonomi di Desa Margacinta, Pangandaran: Training on Processing Local Beverages into Economically Valuable Products in Margacinta Village, Pangandaran - Iskandar, Ridwan; Syadad Saefullah, Moch. Agus; Rusmana, Odang (Politeknik Pariwisata Makassar, 2024)
This community service activity aims to improve basic knowledge of skills in making drinks from plantations and agriculture that grow around the village, as well as to improve the entrepreneurial spirit for managers of Village-Owned Enterprises (BUMDES) and Tourism Awareness Groups (Pokdarwis) in Margacinta Village, Cijulang District, Pangandaran Regency. The activity was carried out at the Karangkamal Hamlet Hall and was attended by 25 participants. The delivery method was carried out using interactive and demonstrative counseling techniques, with the aim of transforming knowledge, attitudes and skills as well as achieving prosperous village communities. The results of the activity showed an increase in the skills and understanding of the participants regarding the utilization and knowledge of plantations and agriculture, namely coconut and honje, which are processed into mixed drinks with the hope that the benefits, uses, processing and results of the drinks contained therein can be obtained. as well as in terms of processing plantation and agricultural products from the garden to being served in a glass, as well as the motivation and follow-up of participants in making, producing and even consuming their own beverage products along with the utilization of other commodities have been successfully improved through this activity.